2017
DOI: 10.18203/2349-2902.isj20172770
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study to predict the severity of acute pancreatitis by BISAP score

Abstract: Background: Acute pancreatitis (AP) is as an inflammation of the pancreas with varied range of complication like peri-pancreatic collection, pancreatic necrosis, renal failure, multi-organ dysfunction syndrome which increases mortality rate and morbidity. Majority of AP cases are mild but severe cases of AP are associated with increased complication and mortality. BISAP is simple bedside prognostic scoring system for predicting severity of AP. BISAP is a collection of simple routine investigation and scores ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…This decreasing trends of mortality can be attributed to scales such as BISAP and Ranson, which have proven to be useful in predicting the prognosis and aiding the management of the patient. 14 In our study, SIRS and severity according to both BISAP and Ranson's score was found significantly correlated. SIRS was present in 42% (n=35) patients, in mild and severe intensity, according to BISAP score 26 and 9, respectively and according to Ranson's score in 21 and 14, respectively.…”
Section: Resultssupporting
confidence: 60%
“…This decreasing trends of mortality can be attributed to scales such as BISAP and Ranson, which have proven to be useful in predicting the prognosis and aiding the management of the patient. 14 In our study, SIRS and severity according to both BISAP and Ranson's score was found significantly correlated. SIRS was present in 42% (n=35) patients, in mild and severe intensity, according to BISAP score 26 and 9, respectively and according to Ranson's score in 21 and 14, respectively.…”
Section: Resultssupporting
confidence: 60%